Silence - Kittisarasuthee, Phra; Thitapanyo, Phramaha Mit (Journal of Graduate MCU KhonKaen Campus, 2022)
We have expected for something to change the situation because we have considered that the current situation is tiring, nothing special nor interesting. Consciousness always has an explanation. It's like a bell that reminds us to stop and listen quietly just by taking a conscious breath in a few seconds. We can be awake to the fact that we are alive and inhaling. We are here and we are still alive. The internal noise will disappear immediately and there will be a feeling of light, airy and profound full of power and tenderness. We can only respond to the calls from the beautiful surroundings around us, “Here I am, I am free, I can hear you.” Therefore, he taught us to be conscious starting with teaching how to take a breath consciously and be aware of every current bodily movement in daily life with the practice.